Beta-2 microglobulin is an amyloidogenic protein in man. - Gorevic, P D (1985)
Curvilinear fibrils with the tinctorial properties of amyloid were isolated from a patient with bone and joint involvement complicating chronic dialysis for renal disease. Subunit fractions of 24,000 and 12,000 mol wt were identified after gel filtration under dissociating conditions, the latter containing a significant amount of a dimer of the former. This was confirmed by Edman degradation of each fraction, which yielded the amino terminal sequence of normal human beta-2 microglobulin (B2M) to residues 20 and 30, respectively. The size of the subunit protein (12,000 mol wt) and the amino acid composition make it likely that intact B2M is a major constituent of the fibrils. B2M is thus another example of a low molecular weight serum protein, with a prominent beta-pleated sheet structure, that may adopt the fibrillar configuration of amyloid in certain pathologic states.